Effects of Weathering on the Release of Heavy Metals from Coal Gangue - Sun, Ya-Qiao; Shen, Yuan-Yuan; Duan, Lei; Dou, Lin (Asian Journal of Chemistry, 2014)
The effect of weathering on the release of heavy metals from coal gangue was revealed. The XRD, SEM and Tessier five-step extraction method were applied to analyze mineral composition, mineral structure and chemical specification of heavy metals from coal gangue. The results showed that after 7-year weathering, the release rate of heavy metals with high mobility, such as Co, Cu and Pb, was 21.69, 36.49 and 36.73 %, respectively. The release rate of Cr and Zn was only 1.46 and 1.32 %, respectively. Both Mn and Fe were enriched and increased by 42.85 and 15.51 % with an increase of S content. Also, the formation of large amounts of iron colloids due to the weathering could facilitate the adsorption and complexation heavy metals. As a result, residual percentage content of heavy metals Cd, Co, Cu, Ni, Pb and Zn increased by 0.52, 12.85, 0.90, 4.53, 3.47 and 0.01 %, respectively.